Optimization of mobile agent procurement performance in an uncertain environment - Sheng, Jin. (2008)
We proposed a flexible architecture that utlilizes a mobile agent and an XML-based electronic catalogue to automate the procurement across a supply chain network to facilitate a buyer's mobile agent to make appropriate decisions in uncertain conditions.